Root-cause analysis of building inspection firm-based problems encountered in Turkish building audit practices - Temizel, Bedirhan; Aladag, Hande (GOLDEN LIGHT PUBL, 2025)
The safety, durability, and sustainability of buildings in T & uuml;rkiye depend heavily on an effective building audit system. However, shortcomings in the enforcement of Law No. 4708 undermine structural safety and increase risks to life and property. This study takes a systematic, evidence-based approach to identify major problems in building inspection firms, analyze their root causes, and propose practical solutions. Using expert interviews, Root Cause Analysis (Ishikawa diagrams), and Pareto analysis, the research identifies key issues such as insufficient qualified personnel, cost-driven processes, and policy gaps. The novelty of this study lies in its focused examination of building inspection firms as a distinct stakeholder group and its application of structured problem-solving tools to building audit practices in T & uuml;rkiye, enabling both a rigorous diagnosis of problems. The association of RCA and Pareto analysis enables targeted, evidence-based strategies to improve inspection quality and prevent the recurrence of deficiencies. Recommendations include strengthening transparency and independence in inspections, raising quality standards, improving training for inspectors, and revising fee structures. The findings offer actionable strategies for T & uuml;rkiye and transferable insights for countries facing similar regulatory challenges, contributing to both theory and practice in construction quality assurance.
Keywords: Building audit issues; Building inspection firms; Root-cause analysis (RCA); Ishikawa diagrams; Pareto analysis; QUALITY; Construction & Building Technology; Engineering